Youth Citizenship: Connected and Unconnected in Public Issues - Laurensius Petrus SAYRANI; David B.W. PANDIE; Melkisedek N.B.C. NEOLAKA (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study is about youth citizenship in the management of public issues. The study based on considerations related to the demographic situation of the population in Indonesia, which is actually dominated by young people. Especially for this study, young people will be placed in two important areas. First, the citizenship of young people and secondly the citizenship of young people who grow up in the context of a region (city) that is economically growing in a moderate range (Kupang City) and a small town (Bajawa City). The main issue raised in this article is how are the conditions and citizenship of young people growing and developing in response to the public issues around them? The method used in this study is a qualitative method based on in-depth interviews, case studies and discussions involving young people ranging in age from 15-25 years. The results of research in these two areas show a tendency for the involvement of young people in public affairs. First, young people in both regions have the ability to define public issues that they consider important. Second, the tendency to use digital media as a forum for organizing and social movements. Digital media allows children's movements which tend to be small, limited. Third, autonomous movement. This independence is especially strongly influenced by their desire not to be interfered with by other groups. Fourth, diametric relations with the government. Even though their efforts are often considered important by the government, they tend to keep their distance from the government.